Sugar Utilization by Saccharomyces cerevisiae in Fermentation to Produce Ethanol - Auni Jamali; Nur Ainul Mardhiah Min; Mohd Noor, Siti Fatimah (Multidisciplinary Applied Research and Innovation, 2024)
This paper influence of sugar utilization by S. cerevisiae in fermentation to produce ethanol. Because a large number of trees have been cleared for palm oil plantations or destroyed, the production of palm oil on a large scale has drawn criticism and worry from the international community. The aims of this research is to identify the content of fructose, glucose, and sucrose in oil palm trunk and compare ethanol production in fermentation using different types of sugar as the main carbon source. Sugar can be characterized by using the DNS method to analyze sugar before further fermentation to see the growth of yeast in the sugar solution. Then to analyze the ethanol production in this research, fermentation has been occurring between glucose, fructose, sucrose, a mixture of sugar and Oil Palm Trunk (OPT) to observe the growth of the baker’s yeast in which sugars is more produced ethanol after 144 hours. So, the sugar that can produce the highest amount of ethanol is OPT. It occurred at the 24th hour with a value of 21.13 mg/mL. The study highlights the importance of optimizing fermentation parameters, such as temperature, pH and oxygen availability, to increase sugar utilization and increase ethanol production.